MANFAAT BEBERAPA JENIS MIKROBA YANG DIISOLASI DARI KAYU LARU (Peltophorum pterocarpum.) DAN MUR SEBAGAI STARTER DALAM PEMBUATAN LARU DAN SOPI DI PULAU TIMOR - Regina I. M BanoEt; I Made Sudana; I.G.N. Alit Susanta Wirya (Journal of Agricultural Science and Biotechnology, 2016)
The traditional knowledge of farmers in producing alcohol from palm sap can be used as a basis to produce high-value economic products such as medical alcohol, industrial alcohol and ethanol. Food products and traditional fermented beverage are one of the main sources to obtain the potential microbe for microbial fermentation industry. Information on the wood of laru role as agents of microbial cultures and mur for a starter in the making of laru and sopi has not been much identified.The research was conducted in three stages. The first stage of the research, namely the microbial isolation of seven basic materials of making laru and sopi. The identification of microbes by using the API 20C AUX kits and a selection of microbes which have the ability to perform fermentation. The second stage of the research is the production test and gin laru utilize the selection and identification of microbes of, to find the best treatment combination that produces the highest alcohol content. The third stage of the research is the identification of molecular of microbes of culture results that have the best fermentation activities. The first and the third stages were exploratory studies by using the experimental design in the laboratory. The data were collected by means of direct observation. The theoretical analysis was made to describe the experimental results. The second stage of the testing of making laru and sopi to determine the percentage of alcohol content produced. The second stage was an experimental study, designed in the basic experimental design of RAL. The obtained data were analyzed with analysis of variance (ANOVA) to determine the real level of treatment effects, followed by LSD test to determine the level of significant differences between treatments. Each treatment combination was repeated four times. Two controls were used i.e; nira, palm sap without addition of a starter, and a solution of sugar with addition of the laru wood starter. The study was conducted in Labotory of Microbiology and Analytical Chemistry of The Food and Drug Administration Center for Kupang, East Nusa Tenggara.The experimental results showed that the microbes of laru wood and Mur are from the group of yeast. For the making of effective laru and sopi which to be sources of the microbes is red Mur and white Laru. The microbial species were identified as Saccharomyces cerevisiae. The resulting alcohol content on the microbes fermentor of Saccharomyces cerevisiae in the test of making red laru was 8.43%, white laru was 7.05%, sopi and nira/palm wine were 21.44%, and sopi from the aer sugar solution was 23.20%. Saccharomyces cerevisiae can also be combined with wood of laru as a starter in the making of laru and sopi. The combination of the two was the best treatment, resulted in the highest alcohol content at 8.90% of red laru, white laru at 8.40%, sopi from nira at 23.38%, and sopi from aer sugar solution at 23.91%.